PENERAPAN NILAI-NILAI UNTUK MENINGKATKAN NASIONALISME PADA ANAK PEKERJA MIGRAN INDONESIA DI MALAYSIA - Nabila, Silvia; Bong, Naiana Talitha; Eldestza, Nabila Zalfani; Ramadhan, Muhammad Fitra Kususma; Syukur, Abd; Raihan, Annisa; Altaira, Ayham; Agusman, Desi Destiana; Azizah, Siti Nur (CV. Alina, 2025)
Indonesian migrant workers' children in Malaysia face challenges in maintaining their national identity. Although the Indonesian language is still used as a daily communication tool, there is a limited understanding of the role of language and the values of Pancasila in fostering a sense of nationalism. In this context, it is essential to design a targeted educational program to enhance national awareness. This research proposes an educational program based on Pancasila values with an interactive approach, such as the use of the 3 Magic Words (